Functional informativeness of lymphocytes’ cytomorphometric analysis of laboratory rats’ blood - Frolov, O. K.; Lytvynenk, R. O.; Makyeyeva, L. V.; Макєєва, Людмила Валеріївна (My University, 2021)
Immunological methods that objectively reflect the lymphogenetic processes in the examined organism are needed to assess the effectiveness of prophylactic or therapeutic agents that modulate regenerative processes in the immune system. Such requirements are met by the cytomorphometric method of analysis of circulating blood lymphocytes, the size (small, medium and large) populations of which reflect their proliferative processes in the lymphoid organs. However, the cytomorphometric characteristics of lymphocytes have species features that have to be determined experimentally. In the model of fecal peritonitis in white non-linear sexually mature male laboratory rats, the limits of statistical size classes of lymphocytes were determined, which were the same in control and experimental animals, namely: small – with a diameter of 8.5 μm and less, medium – with a diameter of more than 8.5 μm and less 11.0 μm, large – with a diameter of 11.0 μm and more. Acute infectious process significantly changed the levels of cytomorphometric classes of lymphocytes according to their functional activity in immunogenesis: small, medium and large size of lymphocytes as 42.5 to 7.0%, 45.0 to 54.0%, 10.5 to 39.0%, respectively, in the control and experimental groups of animals, which demonstrates the informativeness of the method. In this case, small and large lymphocytes belong to the activated lymphocytes, which determine the state of the immune system, while medium lymphocytes mainly make up the pool of memory cells. Based on the ratio of these size classes in the peripheral blood, a conclusion about the proliferative reaction of lymphocytes in the experiment is made, followed by the extrapolation of the results and in clinical practice.
Keywords: Cytomorphometric classes of lymphocytes; experimental peritonitis; state of immunity